Explaining the components of improving the physical and functional quality of the Culture and Arts Center to meet human social needs and promote social interactions - Palangi, Hamed; Jozpirry, Alireza (Technium Social Sciences Journal, 2021)
Objective: The purpose of this study is to explain the components of improving the physical and functional quality of the Culture and Arts Center to meet human social needs and promote social interactions. Objective: The purpose of this study is to explain the components of improving the physical and functional quality of the Culture and Arts Center to meet human social needs and promote social interactions. Research method: The present research method is quantitative and the researcher-made questionnaire is the main tool for collecting information in this research. The main structures of the questionnaire are derived from theoretical foundations. For this purpose, 384 questionnaires were distributed among the statistical sample. Descriptive and inferential statistics were used to analyze the findings in SPSS software as well as Smart PLS. Findings: The findings of this study show that the problem of promoting social interactions and meeting human social needs in Qazvin Culture and Art Center depends on a series of interventions in the functional, aesthetic, identity, physical and environmental areas of space.